Uncovering patterns of technology use in consumer health informatics. (31st August 2013) - Hung, Man; Conrad, Jillian; Hon, Shirley D.; Cheng, Christine; Franklin, Jeremy D.; Tang, Philip
Abstract : Internet usage and accessibility has grown at a staggering rate, influencing technology use for healthcare purposes. The amount of health information technology (Health IT) available through the Internet is immeasurable and growing daily. Health IT is now seen as a fundamental aspect of patient care as it stimulates patient engagement and encourages personal health management. It is increasingly important to understand consumer health IT patterns including who is using specific technologies, how technologies are accessed, factors associated with use, and perceived benefits. To fully uncover consumer patterns it is imperative to recognize common barriers and which groups they disproportionately affect. Finally, exploring future demand and predictions will expose significant opportunities for health IT. The most frequently used health information technologies by consumers are gathering information online, mobile health (mHealth) technologies, and personal health records (PHRs). Gathering health information online is the favored pathway for healthcare consumers as it is used by more consumers and more frequently than any other technology. In regard to mHealth technologies, minority Americans, compared with White Americans utilize social media, mobile Internet, and mobile applications more frequently. Consumers believe PHRs are the most beneficial health IT. PHR usage is increasing rapidly due to PHR integration with provider health systems and health insurance plans. Key issues that have to be explicitly addressed in health IT are privacy and security concerns, health literacy, unawareness, and usability. Privacy and security concerns are rated the number one reason for the slow rate of health IT adoption. WIREs Comput Stat 2013, 5:432–447. doi: 10.1002/wics.1276 This article is categorized under: Applications of Computational Statistics > Computational and Molecular Biology Applications of Computational Statistics > Health and Medical Data/Informatics